2007
DOI: 10.1002/app.25243
|View full text |Cite
|
Sign up to set email alerts
|

Structure and deformation of an elastomeric propylene–ethylene copolymer

Abstract: The elastic behavior of a propylene-ethylene copolymer was investigated. An initial ''conditioning'' tensile extension up to 800% strain resulted in an elastomer with low initial modulus, strong strain hardening, and complete recovery over many cycles. Structural changes that occurred in the low crystallinity propylene-ethylene copolymer during conditioning, and that subsequently imparted elastomeric properties to the conditioned material, were investigated. Thermal analysis, wide and small angle X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…The degree of crystallinity decreases with increasing content of soft segments; thus, the polymer changes from a rigid plastic to a soft elastomer [1][2][3].…”
Section: Open Accessmentioning
confidence: 99%
“…The degree of crystallinity decreases with increasing content of soft segments; thus, the polymer changes from a rigid plastic to a soft elastomer [1][2][3].…”
Section: Open Accessmentioning
confidence: 99%
“…Strain hardening of the SEBS leads to further increase in the stiffness of the substrates upon application of strain, the surface of elastomeric polymer SEBS is quite stiff (*2 MPa) in comparison to the natural environment in which neurons grow. 31,50 The changes in the stiff CP and pristine SEBSsubstrates do not lead to large variations in the formation and maturation of focal adhesion complexes which are primary effectors of cytoskeletal arrangement and other downstream signaling events like cell adhesion and differentiation. CP SEBS substrates allow potential development of implantable electrodes by providing a mechanical environment whose surface conductance can be modulated by application of strain.…”
Section: Discussionmentioning
confidence: 99%
“…The crystalline lamellae traverse the iPP and EB9 phases and appear to remain in registry as they cross these domains. Both Bates et al [23] and Hiltner et al [24] have reported this type of phenomenon previously for blends of iPP with metallocene polyethylene (mPE) copolymer. They attributed the strength of the bond between the two components to the formation of entanglements at the iPP/mPE crystal/crystal interface.…”
Section: The Near-surface Morphology Of Tpomentioning
confidence: 91%